Targeting Ferroptosis: Acteoside as a Neuroprotective Agent in Salsolinol-Induced Parkinson’s Disease Models - Hongquan Wang; Shuang Wu; Qiang Li; Huiyan Sun; Yumin Wang (Frontiers in Bioscience-Landmark)
Background: Salsolinol (SAL) is a dopamine metabolite and endogenous neurotoxin that exerts neurotoxicity to dopaminergic neurons and is involved in the genesis of Parkinson’s disease (PD). However, the machinery underlying SAL-induced neurotoxicity in PD is still being elucidated. Methods: In the present study, we first used RNA-seq and KEGG analysis to examine differentially expressed genes in SAL-challenged SH-SY5Y cells. PD animal models were established and treated with acteoside. Cell viability assays, lipid peroxidation assessments (malondialdehyde [MDA] and 4-Hydroxynonenal [4-HNE]), immunoblot, and transmission electron microscopy were used to confirm acteoside-mediated inhibition of ferroptosis and its neuroprotective effect on dopaminergic (DA) neurons. Results: We found that ferroptosis-related pathway was enriched by SAL. SAL inducing ferroptosis through upregulating long-chain acyl-CoA synthetase family member 4 (ACSL4) in SH-SY5Y cells, which neurotoxic effect was reversed by ferroptosis inhibitors ferrostatin-1 (Fer-1) and deferoxamine (DFO). Acteoside, a phenylethanoid glycoside of plant origin with a neuroprotective effect, attenuates SAL-induced neurotoxicity by inhibiting ferroptosis in in vitro and in vivo PD models through downregulating ACSL4. Conclusions: The present study revealed a novel molecular mechanism underlying SAL-induced neurotoxicity via induction of ferroptosis in PD, and uncovered a new pharmacological effect against PD through inhibiting ferroptosis. This study highlights SAL-induced neurotoxicity via ferroptosis as a potential therapeutic target in PD.